Descriptive Analysis of the 2022 National Defense Index - Levianto, Jubei; Kusuma, Airlangga Surya (Program Pascasarjana Universitas Negeri Makassar, 2024)
The Indonesian nation (NKRI) is facing various national issues, both from external and internal sources, which inevitably affect the nation’s unity and integrity. This is especially evident among the younger generation of Indonesia, who are gradually losing their sense of national defense awareness and patriotism. Conflicts—whether political, social, economic, or cultural—along with demonstrations, mass unrest, and violent acts, all contribute to a potential national disintegration, ultimately leading toward radicalism and separatism movements. To anticipate these issues, an understanding of national defense values is essential. To strengthen national unity and integrity, there is a need to measure national defense readiness through a National Defense Index (NDI). The NDI is a personal assessment of the level of awareness among Indonesian citizens to defend their country, reflected in their attitudes, determination, behaviors, and actions, both individually and collectively. The index’s measurable variables include the five core elements of National Defense: love for the homeland, awareness of nationhood and statehood, loyalty to Pancasila, willingness to sacrifice for the nation and state, and basic capability for national defense. This study found that the National Defense Index (NDI) reached a level of 3.30. The highest-scoring element was willingness to sacrifice for the nation and state (with a score of 3.49), while the lowest was awareness of nationhood and statehood (with a score of 3.04). The implications of this study suggest the need for further cultivation, especially in areas scoring lower, such as awareness of nationhood and statehood.